Pengaruh Label Halal Terhadap Produk Kecantikan - Ananya Larasati; Ikhwan Hamdani; Santi Lisnawati (Al Maal: Journal of Islamic Economics and Banking, 2019)
The purpose of this study is how to use halal labels on decisions purchase of Muslim beauty products in Bogor.  Thiis study uses quantitative research methods. The data sources used are primary and secondary data. The respondents who were sampled in this study were 100 people. The process of data analysis in this study uses simple linear regression analysis.  Significant halal variable labels on purchasing decisions this is seen from the halal significant label of 0,000 which means it is smaller than the significance level used which is 0.05. And it can also be seen from t count of 5.110 which means that the t count is greater than t table which is 1.984. The decision to buy Muslims is based on the label of halal presence on product packaging, the selection of products labeled halal is based on the beliefs and attitudes of Muslim women to buy products labeled halal.